Uma pesquisa exploratória sobre: Quando em conformidade com a norma ANP 19/2015, o etanol combustível brasileiro é corrosivo? - Sousa, Rafael Laurentino Ferreira de (2018)
Fuel ethanol (EHC) is today the main competitor of type C gasoline in Brazil, but to be able to consume this fuel, it needs to be within legal and physical parameters and quantitative and qualitative analyzes will say whether or not the fuel is fit for marketing and consumption. Likewise, when under combustion conditions, it is often questioned whether there is a possibility of EHC corrosion in Otto cycle engines. The ethanol molecule is very similar to water with respect to solubility so that levels of inorganic metal contamination in EHC can give corrosive characteristics depending on the resulting reducing potential. To this end, the ANP, the government body responsible for inspecting all fuels marketed in Brazil, carries out the traceability of the EHC analyzes through a set of several laboratories throughout the country, but not related to corrosion. Therefore, the purpose of this work was to carry out an exploratory research in order to answer the question: if within the limits of conformity to ANP 19/2015, EHC is corrosive. The methodology of exploratory research was based on technical information and foundations found in websites, blogs, journals and scientific journals and mainly ANP standards. It was explored which EHC components possessed some direct or indirect corrosive capacity for metal surfaces. It was sought to explain the norm that regulates the accepted maximum levels and how to make use of it. Also discussed was the compliance bulletin that is monthly carried out by the ANP. Based on the technical information based on the composition of the EHC and the legal conditions of its commercialization, it has been proven that when in accordance with ANP19 / 2015, there is no possibility of corrosion of this fuel to metallic surfaces.